PERANAN MANAJEMEN RISIKO DALAM MEMODERASI RASIO KEUANGAN TERHADAP NILAI PERUSAHAAN - Maychael; Dewi Cahyani Pangestuti (Fakultas Ekonomi Dan Bisnis, Universitas Pembangunan Nasional Veteran Jakarta, 2023)
The aim of this research is to determine the role of Risk Management in moderating financial ratios to firm value, as well as to determine Profitability as proxied by Return On Equity Ratio (ROE), Solvency as proxied by Debt to Equity Ratio (DER), and Liquidity as proxied by Current Ratio ( CR) to Company Value as proxied by Tobins'Q. This study examines the population of property sector companies listed on the Indonesia Stock Exchange (IDX) for the 2018-2021 period. By using purposive sampling, 120 samples were obtained. Data analysis in this study was conducted using Panel Data Regression. The results of this study partially show that, (1) Profitability has an effect on Firm Value, (2) Risk Management does not moderate Profitability on Firm Value, (3) Solvency has an effect on Firm Value, (4) Risk Management does not moderate Solvency on Firm Value (5) Liquidity has an effect on Company Value, (6) Risk Management does not moderate Liquidity on Firm Value. Keywords: Profitability, Solvency, Liquidity, Risk Management, Firm Value